Is expected substance type associated with timing of drug checking service utilization?: A cross-sectional study - Tara Beaulieu; Evan Wood; Samuel Tobias; Mark Lysyshyn; Priya Patel; Jennifer Matthews; Lianping Ti (BMC, 2021)
Abstract Background Drug checking is a harm reduction intervention aiming to reduce substance use-related risks by improving drug user knowledge of the composition of unregulated drugs. With increasing fears of fentanyl adulteration in unregulated drugs, this study sought to examine whether the expected type of drug checked (stimulant vs. opioid) was associated with timing of drug checking service utilization (pre-consumption vs. post-consumption). Methods Data were derived from drug checking sites in British Columbia between October 31, 2017 and December 31, 2019. Pearson's Chi-square test was used to examine the relationship between expected sample type (stimulant vs. opioid) and timing of service utilization. Odds ratios (OR) were calculated to assess the strength of this relationship. The Mantel-Haenszel (MH) test was used to adjust for service location. Results A total of 3561 unique stimulant and opioid samples were eligible for inclusion, including 691 (19.40%) stimulant samples; and 2222 (62.40%) samples that were tested pre-consumption. Results indicated a positive association between testing stimulant samples and testing pre-consumption (OR = 1.45; 95% CI 1.21-1.73). Regions outside of the epicenter of the province's drug scene showed a stronger association with testing pre-consumption (ORMH = 2.33; 95% CI 1.51-3.56) than inside the epicenter (ORMH = 1.33; 95% CI 1.09-1.63). Conclusion Stimulant samples were more likely to be checked pre-consumption as compared with opioid samples, and stimulant samples were more likely to be tested pre-consumption in regions outside the epicenter of the province's drug scene. This pattern may reflect a concern for fentanyl-adulterated stimulant drugs.